The t-transformed power method distributions for simulating univariate and multivariate non-normal distributions. Issue 4 (2nd April 2020) - Pant, Mohan D.
Abstract: This paper introduces a family of t -transformed power method distributions for fitting empirical and theoretical distributions with a wide range of skew and kurtosis values. Equations associated with the first four product moments (mean, variance, skew, and kurtosis) are derived and a methodology is subsequently illustrated for simulating univariate non-normal distributions based on the moment matching approach. Also included is a methodology for generating multivariate non-normal distributions correlated at the user-specified Pearson correlation matrix. The Monte Carlo simulation results indicate that the proposed methodology produces excellent agreement between estimates of Pearson correlations, skew, and kurtosis and their corresponding parameter values.